Tools for chemical product design : from consumer products to biomedicine - Martín, Mariano Martín; Eden, Mario R.; Chemmangattuvalappil, Nishanth G. (Computer-aided chemical engineering ;, 2017)
This book describes the challenges involved in systematic product design across a variety of industries and provides a comprehensive overview of mathematical tools aimed at the design of chemical products, from molecular design to customer products. Chemical product design has become increasingly important over the past decade and includes a wide range of sectors including gasoline additives and blends in the petroleum industry, active ingredients and excipients in the pharmaceutical industry, and a variety of consumer products and specialty chemicals. Traditionally, such products have been designed through trial and error methods, which not only are time-consuming, but more importantly only provide limited knowledge that can be translated into next generation products. --